Detoxification of pyrrolizidine alkaloids by the harvestman Mitopus morio (Phalangidae) a predator of alkaloid defended leaf beetles - Hartmann, Thomas; Häggström, Håkan; Theuring, Claudine; Lindigkeit, Rainer; Rahier, Martine (My University, 2003)
The harvestman Mitopus morio (Phalangidae) is a generalist predator. It is known to prey on larvae of the chrysomelid leaf beetle Oreina cacaliae defended by plant acquired pyrrolizidine alkaloids (PAs). Tracer feeding experiments were performed to determine how harvestmen tolerate protoxic PAs. Minced meat containing either [14C]senecionine or [14C]senecionine N-oxide was fed to M. morio and subsequently feces and bodies were analyzed. Labeled alkaloid N-oxide remained stable and was eliminated almost unaltered with the feces; only 10% was recovered as tertiary PA. In contrast, approximately 80% of labeled tertiary alkaloid (senecionine) ingested with the diet was N-oxidized and eliminated; the remaining 20% consisted of unchanged senecionine and a polar metabolite of unknown structure. Harvestmen process their diet by excreting digestive juice, indicated by bleaching of the meat color. Analysis of the processed diet revealed some N-oxidation of [14C]senecionine, suggesting the gut as the site of N-oxidation. Analysis of the bodies of harvestmen 80 hours after the tracer feeding pulse revealed only trace amounts of the polar metabolite. Neither senecionine nor its N-oxide could be detected in the body extracts. The results are discussed in relation to the strategies of PA adapted insects to avoid accumulation of tertiary PAs in living tissues.
Keywords: Alkaloid sequestration; Detoxification; Chemical defense; Mitopus morio; Oreina leaf beetles; Predation; Pyrrolizidine alkaloids